Digital Economy to Boost Economy Recovery Post-Pandemic: Indonesia's Strategic Position as New Economic Power in Southeast Asia - Tusta Citta Ihtisan Tri Prasidya; Wahyu Candra Dewi (Global South Review, 2022)
The concept of the digital economy is a relatively new term used by Don Tapscott in 1995. Since then, this term has been widely discussed in different environments, and many countries have started transforming into digital economies using various strategies. The COVID-19 pandemic did not even stop the popularity of the digital economy; in fact, it is expected to be the core of economic recovery post-Covid-19, necessarily in Indonesia. Indonesia's massive number of internet users creates the opportunity to promote digitalization and eventually transform into a digital economy environment. In 2021, the digital trade valuation reached IDR 401 Trillion with an increasing preference for online spending habits. Supported by the rapid growth of the digital payment system and digital banking, the digital economy in Indonesia is projected to reach USD 146 billion valuations by the end of 2025. This study aims to discover the progression of the digital economy in Indonesia in regards to accelerating economic recovery post-pandemic covid-19 and how it would affect Indonesia's position in relations with South East Asia Countries. Furthermore, the report will also discuss the challenge and opportunity to transform into a digital society.